Pendidikan Bagi Generasi Emas Indonesia Abad 21: Sebuah Agenda Perubahan Paradigmatik - Daniel Mohammad Rosyid; Masroro Lilik Ekowanti (Proceedings of The ICECRS, 2018)
If the social phenomenon is a reflection of nature's thought, our culture and value system, then the multidimensional crisis afflicting our society today requires us to re-examine our educational philosophy and practice at least the past 40 years. We suffer all the bad influences of industrialization as part of the colonial process, precisely because we adopt the most advanced instrument, namely, mass schooling system with an obsession for quality-based standard as the magic spell. In this digital era, the effort of liberating society from the colonial, pioneer of independence as a condition of the proclamation of independence was a reform of the national education system. We should be scheduled deschooling society. This agenda includes the following: the paradigmatic shift from the school system to learning webs based Self Organized Learning Environment (SOLE); mass schooling to individualized, customized learning; of relevance to quality; of technical competence to the independence of the soul or creativity. This reform was way back on the three pillars of education philosophy of Ki Hajar Dewantara: family, community, and College. New demands upon the role of the teacher in the 21st century is changing.